The Type of Payment and Working Conditions - Kyung Yong Rhee; Young Sun Kim; Yoon Ho Cho (Elsevier, 2015)
Background: The type of payment is one of the important factors that has an effect on the health of employees, as a basic working condition. In the conventional research field of occupational safety and health, only the physical, chemical, biological, and ergonomic factors are treated as the main hazardous factors. Managerial factors and basic working conditions such as working hours and the type of payment are neglected. This paper aimed to investigate the association of the type of payment and the exposure to the various hazardous factors as an heuristic study. Methods: The third Korean Working Conditions Survey (KWCS) by the Occupational Safety and Health Research Institute in 2011 was used for this study. Among the total sample of 50,032 economically active persons, 34,788 employees were considered for analysis. This study examined the relation between the three types of payment such as basic fixed salary and wage, piece rate, and extra payment for bad and dangerous working conditions and exposure to hazardous factors like vibration, noise, temperature, chemical contact, and working at very high speeds. Multivariate regression analysis was used to measure the effect of the type of payment on working hours exposed to hazards. Results: The result showed that the proportion of employees with a basic fixed salary was 94.5%, the proportion with piece rates was 38.6%, and the proportion who received extra payment for hazardous working conditions was 11.7%. Conclusion: The piece rate was associated with exposure to working with tight deadlines and stressful jobs. This study had some limitations because KWCS was a cross-sectional survey.